2012
DOI: 10.1016/j.jad.2011.09.028
|View full text |Cite
|
Sign up to set email alerts
|

Relationships of impulsiveness and depressive symptoms in alcohol dependence

Abstract: Background Depressive symptoms as well as high levels of impulsivity are subjects of special interest in alcohol dependence, as these factors are considered to influence the course of this disorder. However, until now mutual relationships between impulsivity and depression have not been investigated thoroughly in alcohol-dependent patients. Methods By means of the Barratt Impulsiveness Scale (BIS-11) and stop-signal task, levels of impulsivity among 304 alcohol-dependent patients were measured. The stop-sign… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
15
0

Year Published

2012
2012
2022
2022

Publication Types

Select...
6
4

Relationship

0
10

Authors

Journals

citations
Cited by 30 publications
(16 citation statements)
references
References 47 publications
1
15
0
Order By: Relevance
“…It should be noted, however, that these studies were performed with either affective paradigms, assessing inhibition in a negative emotional context, or with the Barratt Impulsiveness Scale Version 11 (BIS-11;Patton et al 1995), a subjective impulsivity questionnaire. Moreover, two studies in AD patients showing that depression (Jakubczyk et al 2012) and anxiety (Karch et al 2008) symptom severity was associated with increased impulsivity excluded AD patients with an established co-morbid depression/anxiety DSM-IV diagnosis. Thus, it remains unclear how depression/ anxiety is related to (non-affective) response inhibition, and especially whether AD patients with co-morbid depression/anxiety disorders resemble patients with depression/anxiety only.…”
Section: Introductionmentioning
confidence: 99%
“…It should be noted, however, that these studies were performed with either affective paradigms, assessing inhibition in a negative emotional context, or with the Barratt Impulsiveness Scale Version 11 (BIS-11;Patton et al 1995), a subjective impulsivity questionnaire. Moreover, two studies in AD patients showing that depression (Jakubczyk et al 2012) and anxiety (Karch et al 2008) symptom severity was associated with increased impulsivity excluded AD patients with an established co-morbid depression/anxiety DSM-IV diagnosis. Thus, it remains unclear how depression/ anxiety is related to (non-affective) response inhibition, and especially whether AD patients with co-morbid depression/anxiety disorders resemble patients with depression/anxiety only.…”
Section: Introductionmentioning
confidence: 99%
“…The disorder often involves affective symptoms, such as in depression, and high levels of impulsiveness [204], and in alcohol-dependent patients a strong relationship exists between depressiveness and impulsiveness [205]. It has been shown that high levels of impulsiveness/impulse control problems seem to elevate vulnerability for development of alcohol dependence, as well as being predictive for poor outcome measures.…”
Section: Introductionmentioning
confidence: 99%
“…Additionally, the association between negative mood and problematic/maladaptive behavior is stronger among more impulsive people (Dvorak, Simons, & Wray, 2011; Karyadi & King, 2011; King, Karyadi, Luk, & Patock-Peckham, 2011; Simons, Dvorak, Batien, & Wray, 2010; Wray, Simons, Dvorak, & Gaher, 2012). Further, depression and impulsivity often co-occur in individuals with substance use disorders (Bickel, Kowal, & Gatchalian, 2006; Jakubczyk et al, 2012). Together, these results suggest that impulsivity coupled with depressive symptoms may contribute to increased risk taking behaviors among individuals who consume alcohol.…”
mentioning
confidence: 99%